1990
DOI: 10.1056/nejm199003223221202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eicosapentaenoic and Docosahexaenoic Acids on Blood Pressure in Hypertension

Abstract: Studies of whether polyunsaturated fatty acids in fish oil--in particular, eicosapentaenoic and docosahexaenoic acids--lower blood pressure have varied in design and results. We conducted a population-based, randomized, 10-week dietary-supplementation trial in which the effects of 6 g per day of 85 percent eicosapentaenoic and docosahexaenoic acids were compared with those of 6 g per day of corn oil in 156 men and women with previously untreated stable, mild essential hypertension. The mean systolic blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
186
2
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(205 citation statements)
references
References 30 publications
11
186
2
5
Order By: Relevance
“…Other studies with very low doses reported (150 mg DHA and 30 mg EPA) a positive effect on systolic pressure but no effect on diastolic blood pressure. 32 The clinical investigations in humans tend to confirm the hypothesis that o3 PUFAs display antihypertensive properties, 25,30,[32][33][34] in spite of some discrepancies. 35,36 In a meta-analysis, Morris et al 31 outlined the variability of experimental factors (dose, group size, duration of the experiment and patient selection) as a major cause of discrepancy.…”
Section: Clinical Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies with very low doses reported (150 mg DHA and 30 mg EPA) a positive effect on systolic pressure but no effect on diastolic blood pressure. 32 The clinical investigations in humans tend to confirm the hypothesis that o3 PUFAs display antihypertensive properties, 25,30,[32][33][34] in spite of some discrepancies. 35,36 In a meta-analysis, Morris et al 31 outlined the variability of experimental factors (dose, group size, duration of the experiment and patient selection) as a major cause of discrepancy.…”
Section: Clinical Studiesmentioning
confidence: 97%
“…30 A high dose supplement with long-chain o3 PUFAs (3-9 g/day) reduces significantly both systolic and diastolic pressure in patients with a moderate hypertension. Similarly, in an intervention study on a group declaring not to consume any fish and displaying a moderate hypertension (systolico180, diastolico110), a fish oil supplement (6 g/day, representing 5 g of EPA þ DHA) reduced significantly both systolic and diastolic blood pressure.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The samples were centrifuged and serum separated and transferred to te¯on lined screwcapped vials within 1±4 h. Serum samples were kept at 4 C for 2±6 h before delivered to the Regional Hospital, University of Trondheim, and stored at 780 C until analysed. The serum phospholipids fatty acids were analysed essentially as described previously (Bùnaa et al, 1990). Serum lipids were extracted with n-butanol (Bjerve et al, 1974) and phospholipids isolated from the lipid extracts using Sep-Pack C18 columns.…”
Section: Blood Sample Analysesmentioning
confidence: 99%
“…The intake of very-long-chain n-3 fatty acids is described in clinical trials (Bùnaa et al, 1990;Sùyland et al, 1994;Brude et al, 1997), selected groups (Bang et al, 1980;Tjùnneland et al, 1993;Nydahl et al, 1996;Hjartaker et al, 1997) and prospective studies (Morris et al, 1995;Ascherio et al, 1995;Dolecek, 1992;Pietinen et al, 1997), but little information is available about the intake of very-long-chain n-3 fatty acids in random samples of populations (Steingrimsdottir et al, 1995). We therefore assessed the intake and sources of very-long-chain n-3 fatty acids and related the intake to socio-demographic and life-style variables in a national dietary survey.…”
Section: Introductionmentioning
confidence: 99%